PRODUCT QUALITY DEVELOPMENT ANALYSIS OF RICE BRAN CAKE BASED ON CONSUMERS’ EXPECTATION - Silvana Maulidah (Socio-Economics/Agribusiness Department, 2017)
This research analyzes consumer expectations for developing product quality of Rice Bran Cake. Quality Function Deployment (QFD) method is employed to ensure the product that entering the production phase will actually able to satisfy the consumer expectations. There are four phases in QFD method, namely; house of quality, parts deployment, process deployment, and production planning. The results coming from applying the four phases of QFD are: consumers require the quality development of Rice Bran Cake and considered price improvement, the addition of flavor, color, aroma, texture, shape, packaging, legality, durability, and net weight. Company’s response to meet the consumer demand towards Rice Bran Cake that produced in the first phase is the addition of flavors, qualified ingredients, making innovative shapes, price adjustment, the addition of weight and size, packaging design, and no chemical preservatives. In the second phase of part deployment, the priorities which should be improved are natural ingredients usage, procurement of qualified ingredients, the addition of halal label, interested flavor, adjustments with other attributes, and the larger cake pan. The quality development designs of Rice Bran Cake that is produced in accordance with the order of weight values of the highest process planning are supply of raw materials, supply of additional materials, the addition of the appropriate flavors, the addition of food coloring, and packaging. Furthermore, the matrix production planning obtained according to the results of importance weight are making various flavors, the supply of qualified ingredients, legality standardization, designing the forms of packaging, hygiene of tools and materials, and accuracy of production equipment.